Eyeing the Beholder - Tobias Lindström (Current Swedish Archaeology, 2025)
Anthropomorphic clay figurines comprise an enigmatic category of finds associated with Pitted Ware culture sites during the latter part of the middle Neolithic period (c. 2900–2300 BC) in the Baltic Sea region. As with most figurative objects, previous research has often been preoccupied with questions of representation, for example focusing on what the figurines might depict. In this paper, the anthropomorphic figurines are instead explored through their physical properties, primarily their ability to look back at their human makers, handlers and onlookers. Considering these figurines as clay beings that have the ability to look back at their viewers shifts the perspective from representation to presentation. This conceptual shift results in a more dynamic picture of human-figurine interactions at Pitted Ware culture sites.